Impaired vasodilation in pregnant African Americans: preliminary evidence of potential antecedents and consequences - Christian, Lisa; Koenig, Julian; Williams, DeWayne P.; Kapuku, Gaston; Thayer, Julian F. (Psychophysiology, 2021)
Significant health disparities exist between African Americans (AA) and European Americans (EA) in hypertension and hypertension-related disorders. Evidence suggests that this is due to impaired vasodilation in AAs. Pregnancy is a potent systemic vasodilatory state. However, differences in vasodilation between AAs and EAs have not been investigated in pregnancy. We sought to examine the effects of pregnancy on vasodilation in AA and EA women and how this might be related to discrimination and low birth weight in their offspring. Hemodynamics [blood pressure (MAP), cardiac output (CO), total peripheral resistance (TPR)] and heart rate variability (HF-HRV) were examined at baseline in 40 pregnant AAs (n = 20) and EAs (n = 20) and matched nonpregnant women (n = 40). The Experiences of Discrimination scale and birth weight were also measured in the offspring of the pregnant participants. Whereas pregnancy was associated with decreased MAP independent of race, AAs showed impaired vasodilation independent of pregnancy status as indicated by greater TPR despite greater HF-HRV. In AAs, but not EAs, reports of fewer incidences of discrimination were associated with greater TPR. Finally, the HF-HRV of EA mothers was inversely related to the birth weight of their offspring but was uncorrelated in AAs. We report novel evidence of impaired vasodilation to an endogenous vasodilatory stimulus in AAs. Higher TPR was related to discrimination in AAs and higher HF-HRV was related to low birth weight in EAs. These findings have implications for understanding the intergenerational transmission of impaired vasodilation in AAs.
"First published: 11 October 2020".- Artikel-Frontdoor
Gesehen am 24.10.2024